What are the Synergies between CORAF and CCAFS? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Abdulai Jalloh - West and Central African council for agricultural research and development (CORAF). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya